Tragiczna noc okupacji niemieckiej : o problematyce „kolaboracji oddolnej” w Generalnym Gubernatorstwie (1939–1945) - Salmonowicz, Stanisław (Studia Iuridica Toruniensia, 2012)
<!--[if gte mso 9]> <![endif]--> The article is an attempt of critical and methodological consideration about a phenomenon of so-called by the author “collaboration from dawn” with German authorities in the years 1939–1945. Author as the legal historian indicates, especially on example of the history of village territories of Little Poland (Małopolska) and Kielce, that a number of pathological phenomena in the attitudes of various Polish communities must be considered and studied in the context of the general framework of the occupation created by Nazi terror. At the same time it is impossible to generalize any phenomenon in this era, also the problem of the tragic Jewish fate, if the comparative perspective of the era and its negative phenomena across Europe occupied by German is entirely omitted. This type of selective look creates an – despite appearances – often subjective and altogether tendentious picture. The issue of aid to the Jews and its narrow limits can`t be detached of the general history of German occupation, which in Poland lasted the longest time and was – in comparison with the German occupation in Western Europe, unusually hard for the whole society. The author as a legal historian also points to specifi c, very unreliable materials of communist justice in the years 1944–1956 (the epoch of Stalinism in Poland), which, without a comprehensive analysis of the sources, may not constitute the sole basis of knowledge of the era. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->